Kematangan Emosi dan Forgiveness pada Remaja Akhir Perempuan yang Mengalami Putus Cinta akibat Perselingkuhan - Hendrika, Eirine Chatrin; Soetjiningsih, Christiana Hari; Murti, Heru Astikasari Setya (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to examine the relationship between emotional maturity and forgiveness among late-adolescent females who experienced breakups due to infidelity. A quantitative correlational approach was employed, involving 114 female university students aged 18–21 who had experienced infidelity in romantic relationships. The instruments used were the Emotional Maturity Scale (EMS) and the Transgression-Related Interpersonal Motivations (TRIM-18). The findings revealed a significant positive relationship between emotional maturity and forgiveness. These results indicate that individuals with higher emotional maturity tend to have a greater capacity to forgive. The study highlights the importance of developing emotional maturity to support emotional healing in young women after breakups caused by infidelity.